Electrochemical Phase Evolution of Metal‐Based Pre‐Catalysts for High‐Rate Polysulfide Conversion - Zhao, Meng; Peng, Hong‐Jie; Li, Bo‐Quan; Chen, Xiao; Xie, Jin; Liu, Xinyan; Zhang, Qiang; Huang, Jia‐Qi (Angewandte Chemie International Edition, 2020)
In situ evolution of electrocatalysts is of paramount importance in defining catalytic reactions. Catalysts for aprotic electrochemistry such as lithium–sulfur (Li‐S) batteries are the cornerstone to enhance intrinsically sluggish reaction kinetics but the true active phases are often controversial. Herein, we reveal the electrochemical phase evolution of metal‐based pre‐catalysts (Co4N) in working Li‐S batteries that renders highly active electrocatalysts (CoSx). Electrochemical cycling induces the transformation from single‐crystalline Co4N to polycrystalline CoSx that are rich in active sites. This transformation propels all‐phase polysulfide‐involving reactions. Consequently, Co4N enables stable operation of high‐rate (10 C, 16.7 mA cm−2) and electrolyte‐starved (4.7 μL mgS−1) Li‐S batteries. The general concept of electrochemically induced sulfurization is verified by thermodynamic energetics for most of low‐valence metal compounds. The electrochemical phase evolution of metal‐based pre‐catalysts (Co4N) to polycrystalline CoSx that are rich in active sites in working Li‐S batteries is revealed. This transformation propels all‐phase polysulfide‐involving reactions and enables stable operation of high‐rate and electrolyte‐starved Li‐S batteries.